Multifunctional Asymmetric Bilayer Aerogels for Highly Efficient Electromagnetic Interference Shielding with Ultrahigh Electromagnetic Wave Absorption - Cheng-Zhang Qi; Peng Min; Xinfeng Zhou; Meng Jin; Xia Sun; Jianjun Wu; Yanjun Liu; Hao-Bin Zhang; Zhong-Zhen Yu (Nano-Micro Letters)
Highlights The multifunctional asymmetric bilayer MXene-graphene oxide (MG)-MXene aerogel with ultrahigh absorption electromagnetic interference (EMI) shielding is constructed by 3D printing and subsequent freeze-drying. The asymmetric bilayer aerogel achieves ultrahigh electromagnetic wave absorption coefficient of 0.95, and maintains a high EMI shielding effectiveness of over 100 dB. The multifunctional asymmetric aerogel with ultrahigh electromagnetic wave absorption, infrared camouflage, solar-thermal heating, and clean-up of organic solvents and spilled crude oil is developed for multi-scenario applications.